RECOGNITION AND ENFORCEMENT OF THE BLOCKCHAIN ARBITRAL AWARDS UNDER THE NEW YORK CONVENTION - Jovanović, Stefan (Pravni zapisi, 2025)
Blockchain technology is reshaping a wide range of sectors, from finance and law to art. The rise of blockchain platforms offering “blockchain arbitration” suggests a shift toward faster, cheaper and decentralized dispute resolution. A key advantage often highlighted is the potential for automatic enforcement of decisions using smart contracts. However, since this is only a possibility, many decisions will be enforced through traditional means. Given the inherently global nature of blockchain arbitration disputes, an important consideration is whether their decisions can be recognized and enforced under the New York Convention. This paper explores whether blockchain arbitration decisions qualify as awards enforceable under the New York Convention and whether their decision-making process meets the Convention’s enforcement criteria. The author recognizes that the procedural aspect of public policy may be undermined by the way decisions are rendered in blockchain arbitrations.